English: English - Arif, Akbarudin; Trikartono , Drajat; Sugiyanto, Sugiyanto; Dewi, Rosma; Setiawan, Eko (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
The article describes the implementation of self-management type III in Surakarta. Based on Presidential Decree 16/2018 Article 18 paragraph (6) letter c, type III is a self-management that is planned and supervised by the Ministry/Institution/Regional Apparatus responsible for the budget and implemented by the Mass Organization. Backdropped by hesitant among local governments to implement it, this research formulates a research question, are there any significant barriers that can cause of local government of Surakarta not to implement Self-Management Type III? Research is conducted through Qualitative Thematic Analysis that includes data collecting, coding, description, and thematic reflection. Three thematic areas to be observed are policy content, procedure, and practice. Data are collected mainly from interviews, documents, researchers’ participation in Usaid-funded Madani programs in Surakarta 2021-2023, and further participation in Bakesbangpol - National and Political Unity Agency in Surakarta’s self-management type III implementation in 2023. Data are also collected from contemporary articles on CSOs and self-management-related issues. The research finds that there are no significant barriers to implementing self-management type III in Surakarta city unless both the local government unit and implementing CSO need to learn and adapt to procedures of implementation and reporting. On specific CSOs' side, they need to improve their legitimacy and specify services.